Relationship Between Plasma Fluoride Levels, Glutathione Peroxidase Activity, Hemoglobin, and Abortion in Rural and Urban Pregnant Women from Settat (Morocco) - Katir Masnaoui, Lalla Asmaa; Rahim, Abdellatif; Bouchab, Habiba; El Amiri, Bouchra; Nasser, Boubker; Abdel Khalid, Essamadi (UI Scholars Hub, 2023)
Background: This study aimed to investigate the relationship between plasma fluoride and hemoglobin levels, glutathione peroxidase (GPx) activity, and abortion among rural and urban pregnant women from Settat province (Morocco). Methods: Blood samples were collected from rural pregnant women who had not undergone abortion (N = 224), rural pregnant women who had an abortion (N = 38), urban pregnant women who had not undergone abortion (N = 163), and urban pregnant women who had an abortion (N = 14). Results: The highest (p < 0.01) plasma fluoride levels and the lowest (p < 0.01) GPx activity were observed in rural pregnant women. In all participants, plasma fluoride levels were significantly higher (p < 0.001), and the GPx activity was significantly (p < 0.001) lower in pregnant women who had an abortion compared with those who did not undergo such process. No significant difference was observed between the hemoglobin levels of all participants. Furthermore, abortion was positively correlated with plasma fluoride levels (p < 0.001) and negatively correlated with GPx activity (p < 0.001) in rural participants. Conclusions: Rural pregnant women had higher plasma fluoride levels and lower GPx activity, which correlated with the increased abortion risk and oxidative stress.